2015
DOI: 10.1074/jbc.m114.606038
|View full text |Cite
|
Sign up to set email alerts
|

Substrate tRNA Recognition Mechanism of Eubacterial tRNA (m1A58) Methyltransferase (TrmI)

Abstract: Background: tRNA methyltransferases specifically recognize substrate tRNAs. Results: To clarify the tRNA recognition mechanism of TrmI, three tRNA species and 45 variants were analyzed in vitro and in vivo. Conclusion: TrmI recognizes the aminoacyl stem, variable region, C56, purine 57, A58, and U60 in the T-loop of tRNA. Significance: Our in vitro experimental results explain the regulation of in vivo methylation levels in tRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 60 publications
(101 reference statements)
2
35
0
Order By: Relevance
“…For instance, TrmI from T. thermophilus preferentially methylates T. thermophilus tRNA Phe than S. cerevisiae tRNA Phe . It was also shown that the access of TrmI to A 58 requires disruption of the interaction between T and D loops, and indeed, disruption of T and D loop interactions accelerates the methylation [42]. In Fig.…”
Section: Recognition Of Trna Substratementioning
confidence: 75%
See 4 more Smart Citations
“…For instance, TrmI from T. thermophilus preferentially methylates T. thermophilus tRNA Phe than S. cerevisiae tRNA Phe . It was also shown that the access of TrmI to A 58 requires disruption of the interaction between T and D loops, and indeed, disruption of T and D loop interactions accelerates the methylation [42]. In Fig.…”
Section: Recognition Of Trna Substratementioning
confidence: 75%
“…Y78 is a good candidate for the stabilization of the flipped-out adenine given its position in the catalytic pocket, the structure and the dramatic decrease of kcat of the TrmI Y78A mutant. D170 is a crucial residue, universally conserved, that makes hydrogen bonds with both the SAM co-factor and the adenine to be methylated [28,42]. We could not obtained co-crystal of the D170A mutant with either SAM or SAH whereas SAM was present in the catalytic pocket in the crystal structure of Y78A mutant and SAH in the wild-type protein structure.…”
Section: Structures Of Trmi Catalytic Mutants (D170a Y78a)mentioning
confidence: 84%
See 3 more Smart Citations